The Role of Active Compounds in Green Betel Leaf (Piper betle L.)as Antibacterial Agents in the Prevention of Dental Caries: A Literature Review - Mutia Soraya; Dinda Khairunasiah Firza; Melanie Amelia Kartika; Sayyidatul Muna; Tsaania Zulkasri; Dhea khairunnisa; Octa Dhea Indraswari; Subhaini (International Journal of Public Health Excellence (IJPHE), 2026)
Dental caries remains one of the most prevalent oral health problems and is primarily associated with cariogenic bacteria, particularly Streptococcus mutans. Although chlorhexidine is considered the gold standard antibacterial agent, its potential side effects have encouraged the exploration of safer natural alternatives. This literature review aimed to analyze the role of active compounds in green betel leaf (Piper betle L.) as antibacterial agents in the prevention of dental caries. Literature was collected from electronic databases including Google Scholar, PubMed, ScienceDirect, Elsevier, and NCBI, with seven selected studies meeting the inclusion criteria. The findings showed that green betel leaf contains several bioactive compounds, including phenols, flavonoids, eugenol, hydroxychavicol, and allylpyrocatechol, which exhibit antibacterial activity through inhibition of bacterial growth, disruption of cell membranes, suppression of biofilm formation, and interference with bacterial cell wall synthesis. Green betel leaf also demonstrated effectiveness against other oral pathogens associated with caries. Although its antibacterial efficacy remains lower than chlorhexidine, green betel leaf shows strong potential as a natural and biocompatible alternative for dental caries prevention